2022
DOI: 10.30827/portalin.vi.22415
|View full text |Cite
|
Sign up to set email alerts
|

The Forging Links project: Knowledge transference using pre-service teachers’ CLIL units with ICT integration

Abstract: Knowledge about CLIL teaching approaches and the effective integration of ICT into learning processes seem paramount to the success of CLIL in different contexts. Nevertheless, research has shown that pre-service and in-service teachers feel unprepared for effective CLIL programme implementation. Recent research has pointed out that material design might be a successful way of improving knowledge and an aid to help teachers realise effective ICT integration efforts. This study reports on the results of a proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Regarding materials, teachers considered subject books to be bad and an obstacle to teaching and learning. This finding is in line with previous research (Banegas, 2016;Coyle et al, 2010;Gondoavá, 2015;Keogh, 2022;Lazarevic, 2022;Meyer, 2010;Pérez-Cañado, 2017Villarreal & Bueno-Alastuey, 2022), stating that there is lack of quality CLIL materials that support the teaching and learning process. Participants in this study reported they were creating or adapting materials for their CLIL subjects that suited their teaching needs…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding materials, teachers considered subject books to be bad and an obstacle to teaching and learning. This finding is in line with previous research (Banegas, 2016;Coyle et al, 2010;Gondoavá, 2015;Keogh, 2022;Lazarevic, 2022;Meyer, 2010;Pérez-Cañado, 2017Villarreal & Bueno-Alastuey, 2022), stating that there is lack of quality CLIL materials that support the teaching and learning process. Participants in this study reported they were creating or adapting materials for their CLIL subjects that suited their teaching needs…”
Section: Discussionsupporting
confidence: 92%
“…They must go beyond the mere provision of content knowledge in another language since they need to facilitate linguistic exposure to the target language (Morton, 2012). However, and despite this relevant role, studies have signalled a general lack of quality CLIL materials (Banegas, 2016;Banegas et al, 2020;Coyle et al 2010;Gondoavá, 2015;Keogh, 2022;Lazarevic, 2022;Meyer, 2010;Pérez-Cañado, 2017Villarreal & Bueno-Alastuey, 2022). As a result, teachers need to adapt materials and become generators of resources that suit both their requirements and their learners' needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some delved into students' experience in CLIL learning with the support of digital technologies (Galitsyna & Yesenina, 2020;Salekhova et al,2019;Zhao et al,2022). Some looked at the use of technology in designing and developing CLIL materials (Villarreal & Bueno-Alastuey, 2022;Zhyrun, 2016;Lavrysh et al, 2021). Others investigated the role of digital technologies in assisting CLIL pre-service teachers' professional development (Adipat, 2021), collaborative tasks and learning-to-learn competence (Garcia-Esteban et al,2021), student's motivation and engagement (Ángel,2015;Zaripova et al, 2019), and learning in a digital environment (Meinecke, 2020;Paliwoda-Pękosz & Stal, 2015).…”
Section: Summary Of Research Methodologies Used In the Studiesmentioning
confidence: 99%
“…All these linguistic elements should be used in any CLIL session in a way that the students can understand. Therefore, PE teachers should be able to identify this essential language and incorporate it into the lessons effectively, ensuring that students understand it, for example, by means of scaffolding strategies, multimodal pedagogical affordances (Coral et al, 2020; Salvador-Garcia et al, 2020) or making use of technology in an appropriate way (Villarreal and Bueno-Alastuey, 2022). Use ‘teacher talk’ effectively .…”
Section: Outlining a Clil Model For Pementioning
confidence: 99%